UNELE ASPECTE ALE „ÎNVĂŢĂMÂNTULUI DE DEZVOLTARE” - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2009)
The article “Some aspects of the „developing education”” written by the senior lecturer at the department of General piano of the Academy of Music, Theatre and Fine Arts Tamara Melnic, analyses the concept of „developing education” as one of the most popular pedagogical concepts worldwide. Implementing the idea of „developing education” in the theory and practice of general piano teaching, the author makes a series of conclusions. The basic one is the idea on the systematic and universal character of „developing education” in general piano teaching at the higher music education, which contributes to professional skills’ development, creative thinking and deeper exploration of the intellectual capacities of a young musician.